MiR‐24 and its target gene Prdx6 regulate viability and senescence of myogenic progenitors during aging. Issue 10 (24th September 2021) - Soriano‐Arroquia, Ana; Gostage, John; Xia, Qin; Bardell, David; McCormick, Rachel; McCloskey, Eugene; Bellantuono, Ilaria; Clegg, Peter; McDonagh, Brian; Goljanek‐Whysall, Katarzyna
Abstract: Satellite cell‐dependent skeletal muscle regeneration declines during aging. Disruptions within the satellite cells and their niche, together with alterations in the myofibrillar environment, contribute to age‐related dysfunction and defective muscle regeneration. In this study, we demonstrated an age‐related decline in satellite cell viability and myogenic potential and an increase in ROS and cellular senescence. We detected a transient upregulation of miR‐24 in regenerating muscle from adult mice and downregulation of miR‐24 during muscle regeneration in old mice. FACS‐sorted satellite cells were characterized by decreased levels of miR‐24 and a concomitant increase in expression of its target: Prdx6. Using GFP reporter constructs, we demonstrated that miR‐24 directly binds to its predicted site within Prdx6 mRNA. Subtle changes in Prdx6 levels following changes in miR‐24 expression indicate miR‐24 plays a role in fine‐tuning Prdx6 expression. Changes in miR‐24 and Prdx6 levels were associated with altered mitochondrial ROS generation, increase in the DNA damage marker: phosphorylated‐H2Ax and changes in viability, senescence, and myogenic potential of myogenic progenitors from mice and humans. The effects of miR‐24 were more pronounced in myogenic progenitors from old mice, suggesting a context‐dependent role of miR‐24 in these cells, with miR‐24 downregulation likely a part of a compensatory response to declining satellite cell function during aging. We propose that downregulation of miR‐24 and subsequent upregulation of Prdx6 in muscle of old mice following injury are an adaptive response to aging, to maintain satellite cell viability and myogenic potential through regulation of mitochondrial ROS and DNA damage pathways. Abstract : Age‐related changes in miR‐24 and its target gene Prdx6 contribute to defective function of myogenic progenitors and muscle regeneration during aging. miR‐24 upregulation and downregulation of its target Prdx6 is associated with an increase in mitochondrial ROS, increase in pH2Ax, decreased cell viability, myogenic potential and increased senescence. During aging, downregulation of miR‐24 in satellite cells and after muscle injury may represent a compensatory mechanism acting to preserve cell viability and myogenic potential